Some Physical, Biological, Hardness, and Color Properties of Wood Impregnated with Propolis - Akcay, Caglar; Ayata, Umit; Birinci, Emre; Yalcin, Mesut; Kolayli, Sevgi (AVES YAYINCILIK A.Ş., 2022)
Propolis is a bee product collected by honeybees from various tree species in nature. It has antifungal, antibacterial, antioxidant, and anticancerogenic properties. Recently, propolis has been used in wood protection area because it has antifungal properties and is a natural and environmentally friendly material. In this study, some deciduous wood species were treated with methanolic propolis extracts. Propolis solutions were prepared by dissolving propolis in methanol in concentrations of 0.5%, 2.5%, 5%, and 8%. These solutions were forced deep into the Scots pine (Pinus sylvestris L.), fir (Abies nordmanniana), and spruce (Picea orientalis L.) woodblocks under vacuum and pressure. Water uptake and water-repellent efficiencies of the woodblocks were tested at 2-, 4-, and 20-hour immersion periods. Sample blocks were tested against wood-destroying house borer (Hylotrupes bajulus) (Coleoptera, Cerambycidae) larvae for 21 weeks. In addition, color changes of woodblocks treated with propolis were determined. According to results obtained in the study, the highest water-repellent efficiency was 61.4% in propolis-impregnated spruce wood at concentration level of 8% during the 2-hour period. These results show that propolis extracts could be used as hydrophobic material for wood. Larvae mortality rates indicated that 8% concentration level was not adequate to overcome H. bajulus larvae or propolis is not effective against H. bajulus larvae. While L* value decreases with the increase of impregnation rate, a* and b* values increase in all wood types. As the impregnation rate increased, the total color difference also increased.
Keywords: Color change; propolis; Treated Wood; Poplar Wood; Decay Fungi; Resistance; Extracts; Performance; water absorption; Hylotrupes bajulus; Color Change; Hylotrupes Bajulus; Larvae; Propolis; Shore D Hardness; Wood; Water Absorption; larvae; shore D hardness; Forestry; SD1-669.5; wood; 15. Life on land